The empirics of China's outward direct investment - Yin-Wong Cheung; Xingwang Qian (Center for Economic Studies and ifo Institute (CESifo), 2009)
We investigate the empirical determinants of China's outward direct investment (ODI). It is found that China's investments in developed and developing countries are driven by different sets of factors. Subject to the differences between developed and developing countries, there is evidence that a) both market seeking and resources seeking motives drive China's ODI, b) the Chinese exports to developing countries induce China's ODI, c) China's international reserves promote its ODI, and d) the Chinese capital tends to agglomerate among developed economies but diversify among developing economies. Similar results are obtained using alternative ODI data. We do not find substantial evidence that China invests in African and oil-producing countries mainly for their natural resources.
Keywords: F21; F36; O53; 330; market seeking; resources seeking; servicing exports; international reserves; agglomeration effect; Direktinvestition; Chinesisch; Internationale Markteintrittsstrategie; Rohstoffversorgung; Welt; China